Tensile Strength of Ice under Triaxial Stresses. - Haynes,F. D. (1973)
An investigation was conducted to determine the effect of a compressive stress on the tensile strength of bubbly polycrystalline ice. One hundred forty-five tests were made in an apparatus of novel design. A cylindrical dumbbell specimen was stressed in axial tension and radial and tangential compression by a hydraulic system which minimized bending stresses. Compression-tension ratios ranging from 0.21 to 10.14 were used for the tests. Tensile strength was found to decrease with an increase in the ratio. At the ratio of 3.155 the tensile strength is about one third the uniaxial value. The test results support the evidence that the Brazil test underestimates the tensile strength for ice. They also indicate that the Brazil test value for ice can be no greater than one third the uniaxial tensile strength. (Modified author abstract)